To Build upon the built. The restoration of abandoned villages in Altoaragon - Marín Gavín, Sixto (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
The group of uninhabited villages in the north of the area of Huesca is the best example of the cultural landscape in the pre-industrial Altoaragon. They all represent the unaltered built-up memory of a more respectful and balanced way of being in contact with the surrounding territory. After decades of abandonment, a significant amount of them has been restored and updated thanks to the improvement of the infrastructures, the increasing awareness about the value of the patrimony and a deep change in the society`s perception of rural world. The revitalization of an abandoned village is a very complex process that involves very different variables: the due reference to pre-existing elements, the study of the territorial context and a clear definition of the requirement specifications in order to ensure the viability of the re-ocupation of the village. All the cases described in this article are a representative sample of different updating processes for obsolete urban schemes, based on the acknowledgment and respect for those tangible and intangible components that make those patrimony elements worthy of protection.